The role of non-starch polysaccharides in determining the air-water interfacial properties of wheat, rye, and oat dough liquor constituents. (August 2020) - Janssen, Frederik; Wouters, Arno G.B.; Meeus, Yannick; Moldenaers, Paula; Vermant, Jan; Delcour, Jan A.
Abstract: Dough gas cell stability is a prerequisite for obtaining breads with high specific volume and homogeneous crumb. The contribution of cereal endogenous non-starch polysaccharides (NSPs) to gas cell stability during wheat, rye, and oat bread making is still unclear. In this work, the aqueous phases from their fermented doughs were isolated as dough liquor (DL) by ultracentrifugation. The foaming, bulk shear rheology, and air-water (A-W) interfacial properties of wheat and rye DLs (treated with and without endoxylanase) and oat DL (treated with and without both lichenase and β-d -glucosidase) were studied. Enzymatic hydrolysis drastically reduced the apparent bulk shear viscosity of the different DLs and resulted in increased and decreased moduli (or magnitude) of the complex A-W interfacial shear viscosities of wheat and rye DLs, respectively. The latter implies that (non-hydrolyzed) rye DL arabinoxylan strengthens the A-W interfacial film consisting of adsorbed proteins and lipids. No measurable A-W interfacial shear viscosities were obtained for oat DL irrespective of whether its β-D-glucans were hydrolyzed or not. This is probably because lipids dominate the oat DL A-W interfaces. The knowledge generated provides a fundamental basis for specifically modifying the composition of the aqueous phase in wheat, rye, and oat doughs to improve the quality of mixed cereal breads. Graphical abstract: Image 1 Highlights: Dough liquor (DL) was isolated from fermented wheat, rye, and oat doughs. DL non-starch polysaccharides were enzymatically hydrolyzed. Air-water interfacial properties of control and enzyme-treated DLs were compared. Arabinoxylan weaken wheat but strengthen rye DL stabilized air-water interfaces. The role of oat DL β-D-glucan is restricted to their viscosifying properties.